Brown Adipose Tissue Activation Is Involved in Atherosclerosis of ApoE−/− Mice Induced by Chronic Intermittent Hypoxia - Wang, Yue; Jiang, Hong-feng; Liu, Bei-bei; Chen, Lei-lei; Wang, Yue; Liu, Xin-yan; Suo, Min; Wu, Xiao-fan (Frontiers in Cardiovascular Medicine, 2021)
Background: Obstructive sleep apnea (OSA) is an atherogenesis factor of which chronic intermittent hypoxia (CIH) is a prominent feature. CIH exposure can sufficiently activate sympathetic system, which acts on the β3 adrenergic receptors of brown adipose tissue (BAT). However, the activity of BAT and its function in CIH-induced atherosclerosis have not been fully elucidated. Methods: ApoE-/- mice were fed with high-fat diet for 12 weeks and grouped into control and CIH group. During the last 8 weeks, mice in CIH group were housed in cages to deliver CIH (12 hours per day, cyclic inspiratory oxygen fraction 5.0-20.9%, 180 seconds cycle). Atherosclerotic plaques were evaluated by Oil Red O, hematoxylin and eosin, Masson staining and immunohistochemistry. Then we conducted immunohistochemistry, western blotting and qRT-PCR of uncoupling protein 1 (UCP1) to investigate the activation of BAT. The level of serum total cholesterol (TC), triglyceride, low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c) and free fatty acid (FFA) were measured. Finally, RNA-Sequencing was deployed to explore the differentially expressed genes (DEGs) and their enriched pathways between control and CIH group. Results: CIH exposure promotes atherosclerotic plaque area with increasing CD68, α-SMA and collagen in plaques. BAT activation is presented during CIH exposure with UCP1 up-regulated. Serum TC, triglyceride, LDL-c and FFA were increased accompanied with BAT activation. HDL-c was decreased. Mechanistically, 43 lipolysis and lipid metabolism-associated mRNA showed different expression profiling between the groups. Calcium, MAPK and adrenergic signaling pathway include the most gene number among the significantly enriched pathways. Conclusion: This study first demonstrated that BAT activation is involved in the progression of CIH-induced atherosclerosis, possibly by stimulating lipolysis.